Enhancing Students’ Translation Skills using Project Based Learning: A Case of An Islamic University - Heldy Ramadhan Putra; Woro Retnaningsih; Arif Nugroho (Ta'dib: Jurnal Pendidikan Islam, 2022)
This study aims to shed some light on the use of Project Based Learning (PBL) in teaching translation at an Islamic university. Involving 35 students of English department, a Classroom Action Research (CAR) in two cycles and semi-structured interview were adopted to examine the effectiveness of PBL and to explore the students’ perspectives toward strengths and weaknesses of the method. The results revealed that PBL was proven effective to enhance students’ translation performances (p-Value 0.000 < 0.05). The results further demonstrated that PBL was an effective method to develop students’ soft-skills such as communicative competence, critical thinking, problem solving ability, and creativity. However, the students also pointed out that doing translation project using PBL method required sufficient time allocation since it based on contexts and experiences as in real working environments. The results contribute to providing fruitful insights for teachers and college authorities to incorporate PBL as an alternative method for teaching translation. Last but not least, it is a worth saying that project based learning is a promising method for teaching translation at university level.